Adsorption of Cadmium and Chromium in Water Body by SBA-15 - Ma, Yu-Qin; Yu, Hui; Li, Xiao-Dong; Zhai, Qing-Zhou; Xu, Jing-Bo (Asian Journal of Chemistry, 2010)
Nanoscale SBA-15 molecular sieve was synthesized by hydrothermal method and modified with ethylenediamine tetraacetic acid. The prepared materials were characterized by powder X-ray diffraction and scanning electron microscopy. The modified SBA-15 was used as sorbents to adsorb the heavy metal ions Cd2+ and Cr6+ in water body. The effects of pH, temperature and adsorption time on the efficiency of adsorption were studied and the optimum adsorptive conditions were confirmed. The results showed that the adsorptive effect of the material is the best and adsorptive ratio reaches 99.0 % when the pH is 4, temperature is 35 ºC and adsorption time is 0.5 h.